Effects of Tributyrin Supplementation on Growth Performance, Insulin, Blood Metabolites and Gut Microbiota in Weaned Piglets - Stefania Sotira; Matteo Dell’Anno; Valentina Caprarulo; Monika Hejna; Federica Pirrone; Maria Luisa Callegari; Telma Vieira Tucci; Luciana Rossi (Animals, 2020)
The aim of this study was to investigate the effects of tributyrin supplementation on the production traits, the main metabolic parameters and gut microbiota in weaned piglets. One hundred and twenty crossbred piglets (Large White × Landrace) were randomly divided into two experimental groups (six pens each; 10 piglets per pen): the control group (CTRL), that received a basal diet, and the tributyrin group (TRIB) that received the basal diet supplemented with 0.2% tributyrin. The experimental period lasted 40 days. Production traits were measured at days 14, 28 and 40. A subset composed of 48 animals (n = 4 for each pen; n = 24 per group) was considered for the evaluation of serum metabolic parameters and hair cortisol by enzyme-linked immunosorbent assay (ELISA), and faecal microbiota by real-time polymerase chain reaction (PCR). Our results showed that the treatment significantly increased body weight (BW) at day 28 and day 40 (p = 0.0279 and p = 0.0006, respectively) and average daily gain (ADG) from day 28 to day 40 (p = 0.046). Gain to feed ratio (G:F) was significantly higher throughout the experimental period (p = 0.049). Even if the serum parameters were in the physiological range, albumin, albumin/globulin (A/G) ratio, glucose and high-density lipoproteins (HDL) fraction were significantly higher in the TRIB group. On the contrary, tributyrin significantly decreased the urea blood concentration (p = 0.0026), which was correlated with lean gain and feed efficiency. Moreover, serum insulin concentration, which has a regulatory effect on protein and lipid metabolism, was significantly higher in the TRIB group (p = 0.0187). In conclusion, this study demonstrated that tributyrin can be considered as a valid feed additive for weaned piglets.